Increase in liver stiffness after transjugular intrahepatic portosystemic shunt is associated with inflammation and predicts mortality - Jansen, Christian; Mueller, Sebastian (Hepatology, 2018)
Transjugular intrahepatic portosystemic shunt (TIPS) efficiently treats complications of portal hypertension. Liver and spleen stiffness might predict clinically significant portal hypertension. This prospective study investigated liver stiffness in patients receiving TIPS regardless of indication. Of 83 included patients, 16 underwent transient elastography immediately before and 30 minutes after TIPS (acute group), while 67 received shear wave elastography of liver and spleen 1 day before and 7 days after TIPS (chronic group) and were followed further. In blood samples obtained before TIPS from cubital, portal, and hepatic veins, levels of several interleukins (IL1b, IL6, IL8, IL10, IL18) and interferon-gamma were analyzed. In 27 patients (5 acute, 22 chronic), it resulted in an increase in liver stiffness of >10%. In 56 patients, liver stiffness decreased or remained unchanged (<10%). Importantly, spleen stiffness measured by shear wave elastography decreased in all patients (chronic group). None of the clinical or laboratory parameters differed between patients with increase in liver stiffness and those without. Of note, patients with increased liver stiffness showed higher overall and/or hepatic venous levels of proinflammatory cytokines at TIPS and higher incidence of organ failure and worse survival after TIPS. C-reactive protein values and increase of >10% in liver stiffness after TIPS were the only independent predictors of mortality in these patients. Conclusion: This study demonstrates that the presence of systemic inflammation predisposes patients to develop increased liver stiffness after TIPS, a predictor of organ failure and death. (NCT03072615) (Hepatology 2018;67:1472-1484).